Synthesis and characterization of a new platinum(II) complex with L-mimosine - Corbi, P. P.; Massabni, Antonio Carlos [UNESP]; Costa-Neto, C. M. (Taylor & Francis Ltd, 2005)
Synthesis and characterization of a new Pt(II)-mimosine complex are described. Elemental, mass spectrometry and thermal analyses for the complex are consistent with the formula [PtCl2(C8H10N2O4)]center dot 1.5H(2)O. C-13 NMR, N-15 NMR and infrared spectroscopy indicate coordination of the ligand to Pt(II) through the N and O atoms in a square-planar geometry. The final residue after thermal treatment was identified as metallic Pt. The complex is soluble in dimethylsulfoxide.
Keywords: platinum(II); L-mimosine; amino acids; metal complex; N-15 NMR